Collaborative Process in Efforts to Reduce Stunting Prevalence in Central Buton Regency - Islamy, La Ode Syaiful; Andriani, Rininta (Buletin Penelitian Kesehatan, 2024)
Introduction: The government has implemented various efforts to address nutritional issues, one of which is the issuance of Presidential Regulation No. 42 of 2013. This regulation governs the National Movement for the Acceleration of Nutrition Improvement, involving collective efforts by the government and stakeholders. To achieve substantial results, stunting reduction efforts must be integrated and converge across multiple sectors. This study aims to describe the collaboration process in stunting reduction, which presents significant challenges in implementation. Methods: A qualitative method with an interactive data-analysis approach was used in this study. The analysis involved three key stages: data reduction, data presentation, and conclusion drawing. Results: The study revealed that the collaboration process begins with face-to-face dialogue, fostering trust and leading to a commitment to the process. This is achieved through mutual understanding and shared benefits. While face-to-face dialogue is progressing, the involvement of diverse stakeholders remains limited. Nevertheless, the actors involved demonstrate mutual trust, a shared vision, and commitment to a joint agenda. In Central Buton Regency, collaboration is essential to address stunting effectively. Conclusion: The study concludes that while face-to-face meetings involve key parties, broader stakeholder participation, such as community leaders, is still lacking. However, mutual trust and a shared vision among existing participants highlight the importance of multisectoral involvement in reducing stunting prevalence